An assessment of single working women's knowledge of fibers and clothing care practices - Lansang, Ma. Asunta Karina M.
The study was conducted to assess single working women's knowledge on fibers and their clothing care practices. Also, this study tackles other related aspects such as satisfaction and considerations on office garments. Subjects were thirty-five single working women of the Presidential Commission on Good Government. They are the sample group representing single working women, ages twenty to thirty-five. This study had four hypotheses and all were accepted. Apparently, from the Analysis of Variance tests done, results of this study, indicate that age is not a factor or is not significant to the self-perception scale of knowledge on fibers, on satisfaction with clothing purchases, and satisfaction with knowledge on care of fibers, fabrics, and garments. A correlation test was also done on the hypothesis that there is no relationship between whether or not the respondents wash their clothes themselves and their score in ranking fibers from coolest to hottest. Findings also indicate that cotton is the fiber most popularly known and favored by the single working women of this study. Majority always and often consider the fiber content of garments when making clothing purchases. With regard to clothing care practices, 91.4% wash their clothes by hand, majority of which use bar soaps. Only 28.6% wash their clothes themselves, however, only one respondent correctly ranked the fibers according to the required temperature setting from coolest to hottest. Evidences show that there is a need for consumer education. It is also recommended that further studies be made regarding knowledge of fibers and clothing care practices, this time with a different set or group of subjects.